ANALISIS PENGARUH MEDIA SOSIAL INSTAGRAM TERHADAP KEPUTUSAN BERKUNJUNG PASCA REVITALISASI KE TAMAN MINI INDONESIA INDAH (TMII) - Claudia Cassandra; Vishnuvardhana S. Soeprapto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the influence of Instagram social media on the decision to visit Taman Mini Indonesia Indah (TMII) after its revitalization. This research uses a quantitative approach by distributing questionnaires to visitors who had visited TMII after the official announcement of the revitalization. The independent variable consists of four dimensions: content quality, interactivity, credibility, and relevance. The data were analyzed using simple linear regression. The results show that three dimensions—content quality, interactivity, and relevance—have a significant effect on the decision to visit, while credibility does not show a significant influence. The coefficient of determination of 90.1% indicates that Instagram has a strong influence on visitors’ decisions. These findings illustrate that Instagram can be an effective promotional tool, particularly in stimulating interest in visiting tourist destinations after revitalization. This study is expected to serve as a reference for destination managers and future researchers in developing digital marketing strategies in the tourism sector.